Сердце из льда: [повесть] / Мария Северская - Северская Мария (Только для девчонок, 2014)
Экземпляры: ф. 24 (20140826) / Инвентарный номер: 48963 / Цена: 126.00 / Авт.знак: С 28 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6